Comparative in vitro activity of tigecycline and other antimicrobial agents against Shigella species from Kuwait and the United Arab of Emirates - Wafaa Jamal; V.O. Rotimi; T. Pal; Agnes Sonnevend; T.S. Dimitrov (Elsevier, 2010)
Summary: Shigella species isolated from stool samples of symptomatic patients of all age groups at the Mubarak Al Kabir Hospital and Infectious Diseases Hospital, Kuwait and Tawam Hospital, UAE during a 2-year period were investigated for their susceptibility to tigecycline and several other antibiotics by determining the minimum inhibitory concentrations (MICs) using the E test method. A total of 100 and 42 strains were collected from UAE and Kuwait, respectively. The extent of drug resistance in the Shigella spp. isolates from these two countries was analyzed by criteria recommended by the Clinical and Laboratory Standards Institute (CLSI). Amikacin, cefotaxime, cefuroxime, ciprofloxacin, imipenem, meropenem, piperacillin-tazobactam and tigecycline had excellent activities against all isolates from UAE and Kuwait with MIC90s of 12, 0.094, 4, 0.012, 0.25, 0.032, 3 and 0.25 μg/ml and 4, 1, 4, 0.125, 0.38, 0.19, 3 and 0.25 μg/ml, respectively. Half of all isolates from both countries were resistant to ampicillin. None of the isolates in Kuwait was resistant to amoxicillin-clavulanic acid compared with 22% in UAE. Resistance to chloramphenicol was recorded in 50 and 36% of the isolates in Kuwait and UAE, respectively. The percentages of non-susceptibility to trimethoprim-sulfamethoxazole and tetracycline were very high in Kuwait and UAE (76% vs. 92% and 76% vs. 98%, respectively). Notably, one isolate, S. flexneri, from UAE had reduced susceptibility to ciprofloxacin (MIC, 0.25 μg/ml). Four (2.8%) of the isolates were ESBL producers by the E test ESBL method but could not be confirmed by PCR using primers for blaCTX-M, blaSHV and blaTEM. In conclusion, Shigella spp. isolated from symptomatic patients in Kuwait and the UAE demonstrated high rates of resistance to the first-line antibiotics but very susceptible to the carbapenems, cephalosporins, fluoroquinolones and tigecycline. Tigecycline holds promise as a potential drug of choice for the therapy of severe shigellosis. Keywords: Tigecycline, In vitro activity, Shigella spp., Kuwait, UAE